1995
DOI: 10.1007/bf00225077
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis in a Dutch family with X-linked recessive congenital stationary night blindness (XL-CSNB)

Abstract: Linkage analysis has been performed in a large

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In two other families (families 3 and 4; Aldred et al 1992), crossovers localized the CSNB gene to the region proximal to DMD, again overlapping with proposed minimal regions for both the CSNB1 and the CSNB2 genes. Reported crossovers in a Dutch family localized the CSNB gene to the region between OTC and DXS1003 (Berger et al 1995); this finding is consistent with segregation of the CSNB1 gene in this family. An affected male in another Dutch CSNB family (Bergen et al 1995) carried a double-recombinant chromosome that localized the CSNB gene to the region between DMD44 and DXS228, which again overlaps with the CSNB1 minimal region.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In two other families (families 3 and 4; Aldred et al 1992), crossovers localized the CSNB gene to the region proximal to DMD, again overlapping with proposed minimal regions for both the CSNB1 and the CSNB2 genes. Reported crossovers in a Dutch family localized the CSNB gene to the region between OTC and DXS1003 (Berger et al 1995); this finding is consistent with segregation of the CSNB1 gene in this family. An affected male in another Dutch CSNB family (Bergen et al 1995) carried a double-recombinant chromosome that localized the CSNB gene to the region between DMD44 and DXS228, which again overlaps with the CSNB1 minimal region.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, recombinant chromosomes in families that have been ex-amined to date have provided location information for X-linked CSNB, but seldom have individual families provided both close proximal and distal limits for a minimal genetic region that contains the disease gene. Data from the few families that are highly informative indicate that a minimum of two loci for X-linked CSNB are possible: one proximal to DXS426 (Bech-Hansen et al 1991) and one in the region distal to DXS1003-TIMP1-DXS426 (Musarella et al 1989;Aldred et al 1992;Berger et al 1995) or DXS228 (Bergen et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Boycott et al, 1998) and CSNB1 (e.g. Berger et al, 1995;Pusch et al, 2001), were identified. Subsequently, two candidate genes (predicted function), present in the linked region, were cloned and confirmed the genetic cause of CSNB2 (CACNA1F (BechHansen et al, 1998;Strom et al, 1998)) and CSNB1 (NYX (BechHansen et al, 2000;Pusch et al, 2000)).…”
Section: Gene Identification Strategiesmentioning
confidence: 99%
“…Two forms of autosomal congenital stationary night blindness (CSNB) have been shown to be allelic to RP: Both CSNB and RP can result from mutations in (1) the rhodopsin gene (Dryja et al 1993;Rao et al 1994); and (2) the gene encoding the [3-subunit of the rod cGMP phosphodiesterase (Gal et al 1994). The refinement of the RP2 critical interval described here may have significant implications for the localization of other inherited X-linked retinal disorders that have overlapping map locations in Xp11.3-Xp11.22 and which may be allelic to RP2 that is, CSNBX (Aldred et al 1992;Bech-Hansen et al 1992;Berger et al 1995) and X-linked progressive cone dystrophy (Hong et al 1994;Meire et al 1994).The identification of DXS6616 as the new proximal flanking marker for RP2 has also enabled us to exclude several genes as potential candidates for this disorder. Four retinally expressed genes have been mapped to the OATL1 region in Xp11.23 by direct selection using an OATL1 YAC to screen a retinal cDNA library (Geraghty et al 1993).…”
mentioning
confidence: 86%